Diario Extra y las noticias que han requerido el derecho a la rectificación y a la réplica (2015 – 2018) - Valderrama Vera, Carlos Alfredo (2020)
This case study is about requests for replication and rectification that increase every day and fill the pages of newspapers, magazines and informational spaces, focusing on the study of the publications of Diario Extra, during the years 2015 - 2018. Its main objective is to determine the types of news that appear on the covers of the media and on the inside of its pages, if they violate the dignity and honor of people in their circulations. Therefore, the informative process of the news of this printed media was analyzed, as established with the (LOC) Organic Law of Communication and in its articles 23 and 24 that protect the rights of the people affected in the news event, the same that place in the first instance the decency of the individual. In this way, with the help of theories from different authors, a theoretical support could be made that was the fundamental pillar of the work. In addition to the use of various investigative techniques to know if they have abided or lacked the rights of rectification and replication; allowing to determine both strength and threats of the environment under study. The diagnosis of this work made it possible to carry out the results and conclusions of the investigation to improve the news when disclosing said information and do not infringe the rights of people, since the honor, honor and dignity of each person.